Chikungunya Outbreak Risks after the 2014 Outbreak, Dominican Republic - Loevinsohn, Gideon; Paulino, Cecilia Then; Spring, Jessica; Hughes, Holly R.; Restrepo, Angela Cadavid; Mayfield, Helen; de St. Aubin, Michael; Laven, Janeen; Panella, Amanda; Duke, William; Etienne, Marie Caroline; Abdalla, Gabriela; et al. (Emerging infectious diseases, 2024)
The 2014 chikungunya outbreak in the Dominican Republic resulted in intense local transmission, with high postoutbreak seroprevalence. The resulting population immunity will likely minimize risk for another large outbreak through 2035, but changes in population behavior or environmental conditions or emergence of different virus strains could lead to increased transmission.